THE EFFECT OF NITROUS OXIDE ON TESTOSTERONE LEVELS IN RATS - Yaşar, M. Akif; Yayla, Tahsin; Erhan, Ömer L.; Özercan, Reşat; İlhan, Nevin; Avcı, Levent (Fırat University, 2001)
Aim: The endocrine function of the testis was carried out by Leydig cells which produce testesterone. In experimental studies, it was demonstrated that N2O had negative effects on spermatogenesis especially in increasing concentrations with respect to time. In this study, we assessed the effects of N2O administration on rats at different exposure times on testesterone levels. Materials and Methods: A total of 55 Wister-Albino rats were kept in specially prepared cown and divided into two groups as study and control. The study consisted of 4 groups: The mixture of 20% O2 and 80% dry air-gas mixture was applied for 30 days to control group (n=10), group I received 10% N2O + 20% O2 and 70% dry air-gas mixture for 10 days (8 hours/day)(n=15), same protocol was applied to group II for 20 days (n=15) and for 30 days to group III (n=15). Results: There was no statistically significant difference between study groups (groups I, II and III) and the control group in respect to body weights, testicular weights and testesterone levels. Conclusion: In our study, there was no change in the levels of testesterone.

Amaç: Testisin endokrin fonksiyonunu Leydig hücreleri yapar ve testosteron salgılarlar. Deneysel çalışmalarda azot protoksitin (N2O) uygulanan zaman ve konsantrasyonla ilişkili olarak spermatogenez üzerine olumsuz etkileri gösterilmiştir. Çalışmamızda sıçanlara farklı sürelerde N2O uygulamasının testosteron düzeylerine etkisini araştırdık. Gereç ve Yöntem: Ellibeş adet Wistar albino cinsi sıçan özel olarak hazırlanan iki ayrı cam kafese kontrol ve çalışma grupları olarak yerleştirildi. Çalışma grupları; %20 O2 + %80 kuru hava gaz karışımının 30 gün süreyle uygulandığı kontrol (n=10), %10 N2O + %20 O2 + %70 kuru hava gaz karışımının 10 gün süreyle (8 saat/gün) uygulandığı Grup I (n=15), 20 gün süreyle uygulandığı Grup II (n=15) ve 30 gün süreyle uygulandığı Grup III (n=15) olmak üzere toplam 4 gruptan oluşmaktaydı. Bulgular: Grup I, Grup II ve Grup III'e ait vücut ağırlıkları, testis ağırlıkları ve testosteron düzeyleri kontrol grubu ile karşılaştırıldığında istatistiksel olarak anlamlı fark bulunmadı. Sonuç: Çalışmamızda serum testesteron seviyelerinde değişiklik görülmemiştir.
SIÇANLARDA AZOT PROTOKSİT'İN TESTESTERON ÜZERİNE ETKİSİ